Designing the Modern Dual-Engine Two-Speed Smart Hybrid Electric Drive Powertrain. (9th June 2022) - Pattanaik, Balachandra; Alagirisamy, Mukil; Karthikeyan, V.; Nallamothu, Ramesh Babu; Samuel, G. Giftson
Abstract : While potential for battery-powered electric vehicles (BEVs) is increasing as the need to minimise greenhouse gas pollution and the utilization of energy production, the restricted driving range and the uninviting market price constitute BEV obstacles to reliable assessment as a conventional car. This paper suggests a double-motor multispeed direct-drive BEV drivetrain to improve average engine running performance in everyday travelling whilst raising any production or control sophistication, effectively saving minimal battery resources and production costs. The characteristics of the proposed drivetrain are first defined through quantitative and visual measurements, which divide the conventional one-engine propulsion to two with different permanent gears to optimise engine performance. Centred on dynamic powertrain modelling in Simulink, the economic change strategy and circulatory system consisting transfer control were planned and checked. Based on the simulation performance, it is stated that substantial increases in energy quality can be accomplished. Thanks to the optimised torque transfer control technique, the vehicle's incredibly low pull is registered during the shifting phase. Finally, it can be inferred that the suggested dual-motor drivetrain is better than the conventional single-motor equivalent in terms of fuel efficiency, driving range, and expense. There is substantial increase in total machine running areas of affordable to solitary machine performance and megacity driving ages, similar to WLTC, FTP-75, and JP 10-15, with 5 to 8 percentage performance enhancement being achieved.